2020
DOI: 10.1136/openhrt-2019-001218
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an integrated heart failure service in a medium-sized district general hospital

Abstract: ObjectivesAssessing the impact of a new integrated heart failure service (IHFS) in a medium-sized district general hospital (DGH) on heart failure (HF) mortality, readmission rates, and provision of HF care.MethodsA retrospective, observational study encompassing all patients admitted with a diagnosis of HF over two 12-month periods before (2012/2013), and after (2015/2016) IHFS establishment.ResultsTotal admissions for HF increased by 40% (385 vs 540), with a greater number admitted to the cardiology ward (23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…There was no significant difference in in-hospital mortality between the 2 cohorts for HFpEF ( P = 0.472). Notably, for HFpEF, 30-day post-discharge mortality decreased from 8.9% (2012/2013) to 3.1% (2015/2016) ( P = 0.032) [ 75 ]. Improved mortality was prominent among cardiology ward patients, possibly due to optimised fluid status and extended inpatient stays [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference in in-hospital mortality between the 2 cohorts for HFpEF ( P = 0.472). Notably, for HFpEF, 30-day post-discharge mortality decreased from 8.9% (2012/2013) to 3.1% (2015/2016) ( P = 0.032) [ 75 ]. Improved mortality was prominent among cardiology ward patients, possibly due to optimised fluid status and extended inpatient stays [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, for HFpEF, 30-day post-discharge mortality decreased from 8.9% (2012/2013) to 3.1% (2015/2016) ( P = 0.032) [ 75 ]. Improved mortality was prominent among cardiology ward patients, possibly due to optimised fluid status and extended inpatient stays [ 75 ]. The Swedish registry data (SwedeHF) [ 44 ] revealed that HFpEF patients on beta-blockers had lower mortality rates at 1, 3, and 5 years (16%, 37%, and 53%, respectively) with an incidence rate of 157 per 1000 patient-years (95% CI: 153–162) compared with non-beta-blocker users.…”
Section: Resultsmentioning
confidence: 99%
“…NICOR recommends that >85% of AHF cases should receive cardiologist input and >60% to be admitted to cardiology, both of which are associated with improved mortality for HFrEF and HFpEF 13 36. AGH exceeded these KPIs, followed by NRS and least with UHCW.…”
Section: Discussionmentioning
confidence: 99%